Cost-effectiveness of three different strategies for the treatment of first recurrent Clostridium difficile infection diagnosed in a community setting. (2nd July 2018) - Lam, Simon W.; Neuner, Elizabeth A.; Fraser, Thomas G.; Delgado, David; Chalfin, Donald B.
Abstract: Objective: A significant portion of patients with Clostridium difficile infections (CDI) experience recurrence, and there is little consensus on its treatment. With the availability of newer agents for CDI and the added burdens of recurrent disease, a cost-effectiveness analysis may provide insight on the most efficient use of resources. Design: A decision-tree analysis was created to compare the cost-effectiveness of 3 possible treatments for patients with first CDI recurrence: oral vancomycin, fidaxomicin, or bezlotoxumab plus vancomycin. The model was performed from a payer's perspective with direct cost inputs and a timeline of 1 year. A systematic review of literature was performed to identify clinical, utility, and cost data. Quality-adjusted life years (QALY) and incremental cost-effectiveness ratios were calculated. The willingness-to-pay (WTP) threshold was set at $100, 000 per QALY gained. The robustness of the model was tested using one-way sensitivity analyses and probabilistic sensitivity analysis. Results: Vancomycin had the lowest cost ($15, 692) and was associated with a QALY gain of 0.8019 years. Bezlotoxumab plus vancomycin was a dominated strategy. Fidaxomicin led to a higher QALY compared to vancomycin, at an incremental cost of $500, 975 per QALY gained. Based on our WTP threshold, vancomycin alone was the most cost-effective regimen for treating the first recurrence of CDI. Sensitivity analyses demonstrated the model's robustness. Conclusions: Vancomycin alone appears to be the most cost-effective regimen for the treatment of first recurrence of CDI. Fidaxomicin alone led to the highest QALY gained, but at a cost beyond what is considered cost-effective.